SHAPED BY TRADITION. ON THE PERSISTENCE OF HAND-MADE POTTERY TRADITIONS IN NORTHERN GAUL, CA. 100 BC–300 AD - De Clercq, Wim (Rei Cretariae Romanae Fautorum Acta, 2024)
The study area covers a large territory, extending from north to south over the modern territories of southwest Holland, Flanders (Belgium) to Northern France. On a geomorphological level, the region is enclosed by the Scheldt estuary to the North, the Lys-Scheldt-basin to the east, the Scheldt-Aa basins to the south and obviously, the North Sea to the West. The soil types within this area can be roughly divided into three main groups, consisting of clayey soils influenced by tidal movements in the coastal and estuarine areas; sandy, acid and therefore less fertile soils between the coast and the Scheldt basin, and finally the more fertile loam-containing soils in the east and south of the study area.